2014
DOI: 10.2147/pgpm.s52806
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of pharmacogenomic studies in tardive dyskinesia associated with patients with psychiatric disorders

Abstract: Pharmacogenomics is the study of the effects of genetic polymorphisms on medication pharmacokinetics and pharmacodynamics. It offers advantages in predicting drug efficacy and/or toxicity and has already changed clinical practice in many fields of medicine. Tardive dyskinesia (TD) is a movement disorder that rarely remits and poses significant social stigma and physical discomfort for the patient. Pharmacokinetic studies show an association between cytochrome P450 enzyme-determined poor metabolizer status and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 161 publications
(184 reference statements)
0
2
0
1
Order By: Relevance
“…TD reduces quality of life and disrupts a patient’s personal, social, and professional function 7 . A recent report showed that the annualized incidence of TD was 5.5% in patients treated with first-generation antipsychotics, and 3.5% in those treated with second-generation antipsychotics 8 , 9 . The incidence of TD with atypical antipsychotics is higher than expected, and underscores the fact that TD remains a significant clinical problem 10 .…”
Section: Introductionmentioning
confidence: 99%
“…TD reduces quality of life and disrupts a patient’s personal, social, and professional function 7 . A recent report showed that the annualized incidence of TD was 5.5% in patients treated with first-generation antipsychotics, and 3.5% in those treated with second-generation antipsychotics 8 , 9 . The incidence of TD with atypical antipsychotics is higher than expected, and underscores the fact that TD remains a significant clinical problem 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Исследования, изучающие ОНВ 609C>T, показали, что аллель T связан с более высоким риском развития АП-индуцированной ТД и более высокими показателями шкалы AIMS в корейской популяции, однако в китайской популяции таких данных не было получено. Это может быть связано с различиями в частоте аллелей в разных этнических группах [32].…”
Section: гены окислительного стресса ген Pip5k2aunclassified
“…Tardive dyskinesia (TD) is a movement disorder caused by dopamine-receptor antagonists (DRAs), such as typical and atypical antipsychotics and antiemetics, including metoclopramide and prochlorperazine 1–7. The uncontrolled abnormal movements of TD can be socially stigmatising, disabling and worsen quality of life 8–10. Clinicians may initially attempt to manage TD by lowering the dose of or discontinuing the causative agent, but this may not be possible, as it could exacerbate symptoms of the existing primary psychiatric disease or worsen TD symptoms 1–3 5…”
Section: Introductionmentioning
confidence: 99%